Effect of structured physical exercise program on older adult's daily living activities and cognitive functions - Abo El Magd, Manal; Zaki, Sahar (International Journal of Advanced Nursing Studies, 2015)
Background: Older adults experience marked physiological and cognitive changes. Literature states that, daily exercising positively effects older adults' both physical and cognitive functioning. Aim: To evaluate the effect of the developed Structured Physical Exercise Program (SPEP) on both older adult's activities of daily living and cognitive functions. Subjects and methods: A quasi experimental design (pre/ post- tests) was utilized for the current study where the older adults' sample served as their own control. The study was conducted at a charity geriatric home (Female section) in Giza Governorate on a convenient sample of 45 older adult females. Data were collected through using three tools; Personal and clinical data assessment sheet, and the two pre-post scales (i.e. Activity of Daily Living scale "ADL" and Nurses’ Observation Scale for Cognitive Abilities "NOSCA"); both scales were already developed and tested before. Results: Data revealed that, after implementation of SPEP, statistically significant differences, indicating improvement, were found between the older adult's ADL and both their age, presence of support network, the number of offspring and medical history. Also Statistically significant difference, indicating improvement, was found between ADL and NOSCA scales among the study sample before and after implementing the SPEP. Conclusion: Both ADL level and cognitive functions of study sample were significantly improved after implementing the SPEP. Regular physical exercising is likely to have positive effect on both older adults' physical and cognitive functioning resulting in higher level of independency. Recommendation: This study recommends wide range application of the developed SPEP on older adults in Egypt.